Karakteristik briket dari tongkol jagung dengan perekat tetes tebu dan kanji - Nasruddin .; Risman Affandy (Balai Riset dan Standardisasi Industri Palembang, 2011)
The research objective is to study the briquette characteristics produced from pressing process with sugarcane molasses and tapioca flour adhesives. Materials used in this study were 20 mesh corn stem, sugarcane molasses adhesive and tapioca flour adhesives. The treatments were consisted of briquettes without adhesive, briquettes with 4% and 7% sugarcane molasses adhesive as well as briquettes with 4% and 7% tapioca flour adhesive respectively using 20 gram of corn stem. The pressing for corn stem into briquettes was conducted by using pressure of 1, 2, 3, 6 and 10 tonf. The tested parameters for briquettes were water content by using gravimetric method, specific gravity by using gravimetry method and calory value by using bomb calorimeter. The results showed that treatment of 20 gram corn stem with 7% tapioca flour adhesive at 10 tonf pressure had water content of 6.245%, specific gravity of 1.31 g/cm3 and calory value of 4.791 calory/g, respectively.Keywords : Corn stem, sugarcane molasses adhesive, tapioca flour adhesive, briquette AbstrakPenelitian ini bertujuan untuk mempelajari karakteristik briket yang dihasilkan dari proses pengempaan dengan perekat tetes tebu dan perekat kanji. Bahan yang digunakan terdiri dari tongkol jagung ukuran 20 mesh, perekat tetes tebu dan perekat kanji. Briket yang dihasilkan merupakan variasi perlakuan tanpa bahan perekat, dengan perekat tetes tebu 4% dan 7% dari 20 gram berat tongkol jagung, dan dengan bahan perekat kanji 4% dan 7% dari 20 gram berat tongkol jagung. Proses pengempaan tongkol jagung menjadi briket dilakukan pada gaya tekan pengepresan dengan variasi gaya tekan 1, 2, 3, 6, dan 10 tonf. Pengujian briket meliputi kadar air dengan metode oven, berat jenis dengan metode gravimetri dan nilai kalor dengan bomb kalorimeter. Hasil uji menunjukkan untuk perlakuan 20 gram tongkol jagung menggunakan perekat kanji 7% pada gaya tekan pengempaan 10 tonf mengandung kadar air 6,245%, berat jenis 1,31 g/cm3 dan nilai kalor 4.791 kal/g.Kata Kunci : Tongkol jagung, tetes tebu, kanji, briket